Effect of constraint-induced movement therapy in reducing severity of mirror movements in children with unilateral spastic cerebral palsy - Shahid, Javeria; Hussain, Mir Arif; Khan, Huma (Journal of the Pakistan Medical Association, 2023)
To determine the effect of constraint-induced movement therapy (CIMT) in improving hand function and reduction in severity of mirror movements in children with unilateral spastic cerebral palsy who have mirror movement disorder. Spastic hemiplegic CP children of either gender, aged 6 to 16 years, with mirror movements of grade 1 and 2 who were able to make a gross grip, were included in this single arm feasibility study. CIMT was provided as an intervention to these children for six hours per day for 15 consecutive week days. Woods and Teuber criteria was applied for the assessment of mirror movements. Pre- and post-intervention assessment results showed that there was improvement in the unimanual and bimanual hand function in CP-affected children (p< 0.05) and reduction in the severity of mirror movements (p<0.05). Constraint-induced movement therapy improved hand function and reduced the severity of mirror movements in children with unilateral spastic cerebral palsy.